2023
DOI: 10.35848/1347-4065/acbbd3
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration of aerosol using small equipment with two small aerial ultrasonic sources

Abstract: We have developed an ultrasonic agglomeration device that is considerably smaller than previous devices. We used a round-groove small aerial ultrasonic source, which is a compact, intense aerial source of ultrasonic waves. This ultrasonic source generates a large transverse vibration displacement using a circular vibrating plate with a round groove near the tip of the transmission rod, and it produces intense sound waves perpendicular to the vibration plane. In this paper, a compact agglomeration device contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The welding strength obtained with planar vibration was greater than that obtained with linear vibrations. (5) Comparing this study and conventional ultrasonic complex vibration sources showed that similar welding strengths were obtained under the similar conditions. 30) These results demonstrate that the vibration source can be made smaller than the conventional vibration source and that it has become easier to design the amplitude of longitudinal vibration and torsional vibration.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The welding strength obtained with planar vibration was greater than that obtained with linear vibrations. (5) Comparing this study and conventional ultrasonic complex vibration sources showed that similar welding strengths were obtained under the similar conditions. 30) These results demonstrate that the vibration source can be made smaller than the conventional vibration source and that it has become easier to design the amplitude of longitudinal vibration and torsional vibration.…”
Section: Discussionsupporting
confidence: 64%
“…Ultrasonic vibration is widely used for non-contact and nondestructive inspection and measurement [1][2][3][4][5][6][7][8][9] and for applications including ultrasonic welding and ultrasonic processing. [10][11][12] Ultrasonic welding does not require the application of external heat to the objects for welding; thus, this method is suitable for welding dissimilar metals that cannot be welded by hot welding methods due to their different melting points.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that both chemical [6] , [7] , [8] and physical methods [9] , [10] , [11] , [12] , [13] , [14] can offer effective manipulation/treatment of aerosol particles. In the latter, the physical methods include the use of turbulence/vortex [9] , [11] , [15] , magnetics [12] , [16] , electrics [14] , [17] , [18] , and acoustics [1] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] for aerosol particle manipulation. Among them, the acoustic manipulation method, specifically acoustic agglomeration (AA), harnesses sound waves to cause additional motions and collisions of aerosol particles to achieve particle coagulation [1] .…”
Section: Introductionmentioning
confidence: 99%
“…However, audible sound with high SPLs may cause serious noise issues and damage to human hearing especially when there are operators around AA processes. Therefore, the use of airborne ultrasound for further development of AA has been highlighted [30] , and some researchers have successfully established and deployed efficient ultrasonic systems to substitute audible speakers for AA of aerosol particles [21] , [39] , [40] .…”
Section: Introductionmentioning
confidence: 99%
“…In fluids, the effects of cavitation on living organisms have been investigated. 7,8) Technologies that use aerial ultrasonic energy include ultrasonic agglomeration, 9,10) ultrasonic drying, 11,12) and ultrasonic atomization. [13][14][15][16][17][18] Liquids can also be atomized by applying heat, but this method may cause physical and chemical changes in the liquid.…”
mentioning
confidence: 99%